Dl-NBP (Dl-3-N-Butylphthalide) Treatment Promotes Neurological Functional Recovery Accompanied by the Upregulation of White Matter Integrity and HIF-1α/VEGF/Notch/Dll4 Expression - Wang, Yanping; Shen, Yufei; Liu, Ziyun; Gu, Jingxia; Xu, Congying; Qian, Shuxia; Zhang, Xiaoling; Zhou, Beiqun; Jin, Yuhua; Sun, Yanyun (Frontiers in Pharmacology, 2020)
Dl-3-n-butylphthalide (dl-NBP) was approved by the FDA of China for the treatment of acute ischemic stroke. Dl-NBP has been shown to promote neurological functional recovery and enhance white matter integrity using an endothelin-1-induced focal permanent cerebral ischemia model, which could mimic those patients who have no opportunity to receive either tissue plasminogen activator (tPA) thrombolysis or endovascular therapy. However, it is not clear whether dl-NBP could promote neurological functional recovery in a focal transient cerebral ischemia model, which could mimic those patients who have the opportunity to receive either tPA thrombolysis or endovascular therapy. In this study, using a model of middle cerebral artery occlusion in mice, we aim to explore the effect of two-week dl-NBP treatment on neurological functional recovery after ischemic stroke as well as its underlying mechanism. Our results showed that dl-NBP treatment promoted functional recovery assessed by neurological scores and an adhesive remove test, and this improved the integrity of white matter after 60-min ischemia and 14-day reperfusion. In addition, dl-NBP increased the number of RECA-1 positive vessels and enhanced the expression of the tight junction protein occludin. More importantly, dl-NBP also promoted the expression of hypoxia-induced factor-1α, the vascular endothelial growth factor, Notch, and delta-like ligand 4. In conclusion, our study provides evidence that dl-NBP treatment could also promote functional recovery after focal transient ischemia stroke, and this recovery is associated with upregulated white matter integrity, microvessels, and the tight junction protein occludin. Our results suggested that, in future, dl-NBP may also be applied in clinic to promote functional recovery during the later phase of focal transient ischemic stroke.